The Impact of Sanctions on Iran: An Effective Policy? - Sadegh, Atena (Université d'Ottawa | University of Ottawa, 2012)
This Major Research Paper analyzes the theory and practice of sanctions on Iran. The focus of this paper is to evaluate the effectiveness of sanctions as a tool of foreign policy to impede Iran from pursuing its nuclear development program. The goal of the current sanctions as a whole is to impose enough financial and trade barriers on Iran to force them to give up their suspicious nuclear development program. To date, the sanctions imposed on Iran have reached an unprecedented level of international commitment. However the sanctions have not achieved the results desired by the international community. While the economy of the country is collapsing both as a result of sanctions and internal economic mismanagement, and there is growing amount of international pressure on Iran to put an end to its nuclear program, the ayatollahs of the Islamic Republic are reluctant to give in. Moreover, reformist Iranians (politicians, activists and ordinary citizens) are losing economic and political power within the country. According to recent reports by the International Atomic Energy Agency (IAEA), time is running out before Iran develops nuclear weapons capabilities. The potential of a war between Israel and Iran is increasing as the former will not accept a nuclear armed Iran.